Analysis of the quality of hotel services in the canton of Sucre - Villacis Zambrano, Lilia; Macías Barberán, José Ricardo; Meneses Pantoja, William Renan; Espinoza Arauz, Mayra (Journal of business and entrepreneurial studie, 2021)
The hotel sector of canton Sucre has deficiencies in its infrastructure, especially in old buildings, the hotels were not built with all the technical standards. Additionally, they have deficiencies in quality standards and in the preventive maintenance of their facilities, which constitutes the greatest difficulties in offering the destination to the national and international market. The purpose of the study was to establish an improvement program to increase the quality of hotel services and positively influence the economic and tourist development of the city. The methodology used was descriptive, qualitative and quantitative methods with a sample of 30 tourists, which were tabulated through the SPSS Statistic, drawing conclusions that allowed analyzing the flaws of the hotels. The results obtained allowed verifying the deficiencies in the hotel infrastructure, little training for the personnel who work in hotel establishments. So they do not have the technical knowledge in Hospitality, therefore it does not guarantee the quality that must be offered to tourists, intensifying since the 2016 earthquake and recent rains